Opportunities for Improving Antimicrobial Stewardship: Findings From a Prospective, Multi-Center Study in Three Low- or Middle-Income Countries - Muro, Florida J.; Lyamuya, Furaha S.; Kwobah, Charles; Bollinger, John; Bodinayake, Champica K.; Nagahawatte, Ajith; Piyasiri, Bhagya; Kurukulasooriya, Ruvini; Ali, Shamim; Mallya, Rose; Rolfe, Robert; Ruwanpathirana, Anushka; et al. (Frontiers in Public Health, 2022)
Background: To develop effective antimicrobial stewardship programs (ASPs) for low- and middle-income countries (LMICs), it is important to identify key targets for improving antimicrobial use. We sought to systematically describe the prevalence and patterns of antimicrobial use in three LMIC hospitals. Methods: Consecutive patients admitted to the adult medical wards in three tertiary care hospitals in Tanzania, Kenya, and Sri Lanka were enrolled in 2018- 2019. The medical record was reviewed for clinical information including type and duration of antimicrobials prescribed, indications for antimicrobial use, and microbiologic testing ordered. Results: A total of 3149 patients were enrolled during the study period: 1103 from Tanzania, 750 from Kenya, and 1296 from Sri Lanka. The majority of patients were male (1783, 56.6% overall) with a median age of 55 years (IQR 38-68). Of enrolled patients, 1573 (50.0%) received antimicrobials during their hospital stay: 35.4% in Tanzania, 56.5% in Kenya, and 58.6% in Sri Lanka. At each site, the most common indication for antimicrobial use was lower respiratory tract infection (LRTI; 40.2%). However, 61.0% received antimicrobials for LRTI in the absence of LRTI signs on chest radiography. Among patients receiving antimicrobials, tools to guide antimicrobial use were under-utilized: microbiologic cultures in 12.0% and microbiology consultation in 6.5%. Conclusion: Antimicrobials were used in a substantial proportion of patients at tertiary care hospitals across three LMIC sites. Future ASP efforts should include improving LRTI diagnosis and treatment, developing antibiograms to direct empiric antimicrobial use, and increasing use of microbiologic tests.